MICRO WAQF BANK: IMPLICATIONS FOR WAQF LAW IN INDONESIA - Hidayatullah, Hidayatullah; Nasrullah, Nasrullah; Muhammad, Muhammad; Kristiyawan, Ary Chandra (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The Micro Waqf Bank (BWM) initiative in Indonesia aims to expand financial inclusion for low-income communities, particularly around Islamic boarding schools (pesantren). By providing Sharia-compliant microfinancing, BWM supports micro-entrepreneurs who face barriers in accessing conventional banking services. However, the use of the term “waqf” in BWM's branding raises significant legal implications concerning Indonesia's waqf law. Traditionally, waqf assets are meant to be managed perpetually, with the principal maintained intact and only the benefits utilized. BWM’s rotational fund management system deviates from this concept, causing potential misunderstandings among the public about the legal status of waqf within BWM. This study utilizes a normative legal research method, examining statutes and regulatory frameworks to analyze BWM's compliance with waqf regulations. Key findings highlight that BWM operates under Sharia microfinance regulations but is not recognized as a waqf institution under Law Number 41 of 2004 on Waqf, leading to regulatory overlaps and legal ambiguity. The paper recommends harmonization between the Financial Services Authority (OJK) and the Ministry of Religious Affairs to clarify the regulatory status of BWM, ensuring legal certainty and public understanding of waqf and Sharia-compliant finance.